A Sandwich‐Like Organolead Halide Perovskite Photocathode for Efficient and Durable Photoelectrochemical Hydrogen Evolution in Water. Issue 22 (28th May 2018) - Zhang, Hefeng; Yang, Zhou; Yu, Wei; Wang, Hong; Ma, Weiguang; Zong, Xu; Li, Can
Abstract: Organolead halide perovskite materials have demonstrated great potential in the solar cells field owing to their excellent optoelectronic properties. However, the instability issue of the perovskites impedes the translation of their attractive features for the solar fuel production such as photoelectrochemical H2 production from water splitting. Herein, CH3 NH3 PbI3 a photocathode with a sandwich‐like structure is fabricated with a general and scalable approach toward addressing this issue. The photocathode exhibits an onset potential at 0.95 V versus reversible hydrogen electrode (RHE) and a photocurrent density of −18 mA cm −2 at 0 V versus RHE with an impressive ideal ratiometric power‐saved efficiency of 7.63%. More impressively, the photocathode retains good stability under 12 h continuous illumination in water at wide pH range. This performance is much superior to that of the best perovskite‐based photoelectrode ever reported. Abstract : A sandwich‐like CH3 NH3 PbI3 photocathode is prepared with a general and scalable strategy and demonstrates state‐of‐the‐art performance for photoelectrochemical (PEC) H2 production from water splitting among organolead halide perovskite‐based PEC devices. More impressively, the photocathode retains good stability under 12 h continuous illumination in water at wide pH range.